The Story of Mr. And Mrs. Deaf: Deaf American Historiography, Past, Present, and Future - Gienow-McConnell, Haley (Critical Disability Discourses, 2016)
This paper offers a review of deaf American historiography, and proposes that future scholarship would benefit from a synthesis of historical biography and critical analysis. In recent deaf historical scholarship there exists a tendency to privilege the study of the Deaf community and deaf institutions as a whole over the study of the individuals who comprise the community and populate the institutions. This paper argues that the inclusion of diverse deaf figures is an essential component to the future of deaf history. However, historians should not lapse in to straight-forward biography in the vein of their eighteenth and nineteenth-century predecessors. They must use these stories purposefully to advance larger discussions about the history of the deaf and of the United States. The Deaf community has never been monolithic, and in order to fully realize ‘deaf’ as a useful category of historical analysis, the definition of which deaf stories are worth telling must broaden. Biography, when coupled with critical historical analysis, can enrich and diversify deaf American historiography. Le présent article offre un résumé de l'historiographie de la surdité aux États-Unis, et propose que dans le futur, la recherche bénéficierait d'une synthèse de la biographie historique et d’une analyse critique. Il existe une tendance au sein du travail académique récent sur l’histoire de la surdité à privilégier l'étude de la communauté Sourde et des institutions Sourdes, et de négliger l'étude des individus qui constituent la communauté et qui peuplent ces institutions. L'auteur montre ici que rien n'est plus important pour avancer l'histoire des personnes sourdes que l'inclusion d'une diversité de figures sourdes. Cependant, les historiens doivent éviter la tendance – au risque de ressembler à leurs prédécesseurs du 19ème et 18ème siècles – des biographie simples. Ils doivent plutôt utiliser ces récits de façon délibérée pour avancer des discussions plus larges sur l'histoire des personnes sourdes et l'histoire des États-Unis. La communauté Sourde n'a jamais été monolithique, et pour mieux mobiliser cette appellation en tant que catégorie d'analyse historique, la définition des histoires Sourdes qui méritent d’être racontées doit être élargie. La biographie, lorsqu'elle est combinée à une analyse historique critique, peut enrichir et diversifier l'historiographie de la surdité aux États-Unis.